Designing a rating system based on competencies for the analysis of the university teachers' research activities - Nataliia V. Morze; Oksana P. Buinytska; Valeriia A. Smirnova (Academy of Cognitive and Natural Sciences, 2022)
One of the indicators of the influence and competitiveness of university is participation in international and local rankings. In the methodologies of the most authoritative rankings, the quality and transparency of Universities is assessed by indicators of the university teachers' publishing activity. The article analyzes the experience of designing systems that analyses university teachers research activities, tools and components of evaluating the effectiveness of research, designed a structural and functional model of rating system for the analysis the university teachers' research activities taking into account research and digital competencies. The developed model provides performance of the basic functions and allows for systematic monitoring of openness, transparency, efficiency of the research component of university teachers' professional activity. The model was based on key indicators for evaluating the effectiveness of research -- citation indicators of the three most important scientometric databases -- Scopus, Web of Science, Google Scholar. The connection between the indicators presented in the model forms a portrait of the university teachers' scientific activity, gives an overall assessment of productivity, influence and contribution to the research direction of the university as a whole. The article describes 1 stage of implementation of the presented model by developing a "Rating of Transparency of Structural Units", the effectiveness of experimental ranking. The study has established the positive impact of the implementation of the rating system, identified the main activities to increase the visibility, presence, dissemination of research results, the systematic implementation of which contributes to the optimal representation of the scientist in the rating evaluation of the research component of the university teachers professional activities, improving the digital competence of teachers and positively affects the quality indicators of the university scientific work in local and international rankings, as the existence of the system and the formation of ratings is an incentive for university teachers to present and disseminate their own publishing activities in the international online scientific community.